2015
DOI: 10.1007/s12539-015-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Type II Toxin-Antitoxin Loci in Klebsiella pneumoniae Genome Sequences

Abstract: Klebsiella pneumoniae is an increasingly important bacterial pathogen to human. This Gram-negative bacterium species has become a serious concern due to its dramatic increase in the levels of multiple antibiotic resistances, particularly to carbapenems. The toxin-antitoxin (TA) system has recently been reported to be involved in the formation of drug-tolerant persister cells. The type II TA system is composed of a stable toxin protein and a relatively unstable antitoxin protein that is able to inhibit the toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Some RelBE-like TA systems were also distributed in a manner different from that for the K. pneumoniae RelBE systems (59). Thus, the distributions of RelBE_1kp and RelBE_2kp loci differ in plasmids and chromosomes, although they were found in the same K. pneumoniae isolate (16,373). However, a detailed distribution and the implications for the development of a persistence phenotype in K. pneumoniae are unknown (373).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some RelBE-like TA systems were also distributed in a manner different from that for the K. pneumoniae RelBE systems (59). Thus, the distributions of RelBE_1kp and RelBE_2kp loci differ in plasmids and chromosomes, although they were found in the same K. pneumoniae isolate (16,373). However, a detailed distribution and the implications for the development of a persistence phenotype in K. pneumoniae are unknown (373).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 97%
“…Klebsiella pneumoniae isolates have a major role in antibiotic resistance, and the genes for several type I and II TA systems (Hok/Sok, PemK/PemI, and CcdA/CccB) (16) have previously been identified on resistance plasmids carried by this bacterium (372). A bioinformatics approach was used to analyze the distribution of the locus of the type II system and to determine the variability in the TA loci from 10 complete sequenced genomes of K. pneumoniae, revealing numerous putative type II TA loci (373). Some RelBE-like TA systems were also distributed in a manner different from that for the K. pneumoniae RelBE systems (59).…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…K. pneumoniae devises various strategies to adapt to the action of various antimicrobial compounds, including TA system regulation (Navon-Venezia et al, 2017). In our previous in silico work, 212 putative type II TA loci were identified in 30 replicons of completely sequenced K. pneumoniae strains (Wei et al, 2015). Notably, the toxins containing the GNAT domain were prevalent.…”
Section: Introductionmentioning
confidence: 98%
“…Through subsequent validation, we have found that the organisation of SAS genes into bicistronic architectures along with a downstream -or in one case upstream -gene is a strong indicator of toxicity. Identification of bicistronic architectures has been used as a starting point for prediction of TAs previously (44,45). However, these studies have focussed on species that do not encode toxSASs, and therefore these TA systems were not detected.…”
Section: Discussionmentioning
confidence: 99%